Prettier Concurrency: Purely Functional Concurrent Revisions - Leijen, Daan; Burckhardt, Sebastian; Fahndrich, Manuel (Haskell Symposium 2011 (Haskell'11), 2011)
This article presents an extension to the work of Launchbury and Peyton-Jones on the ST monad. Using a novel model for concurrency, called "concurrent revisions", we show how we can use concurrency together with imperative mutable variables, while still being able to safely convert such computations (in the Rev monad) into pure values again. In contrast to many other transaction models, like software transactional memory (STM), concurrent revisions never use rollback and always deterministically resolve conflicts. As a consequence, concurrent revisions integrate well with side-effecting I/O operations. Using deterministic conflict resolution, concurrent revisions can deal well with situations where there are many conflicts between different threads that modify a shared data structure. We demonstrate this by describing a concurrent game with conflicting concurrent tasks.